Determinação da temperatura em elementos estruturais externos de aço em situação de incêndio - Evelyn Tait (2001)
The behaviour of steel structures under fire conditions, and its protection, has only recently deserved attention on the public authorities and researchers part in Brazil. However, the actual Brazilian code NBR 14323, about the issue, published in 1999, does not present a specific procedure to be followed for the temperature reached in structural steel elements on the exterior of a building under fire conditions. This actual work has as references mainly a paper of Margaret Law, Fire safety of external building elements the design approach issued in 1978, Part 1-2 of Eurocode 3, published by CEN as a European Prestandard (ENV) in 1995 and a design guide for fire-safe structural steel published by the American Iron and Steel Institute in 1979. The objectives of this work are to determine the mentioned temperature, including the characteristics of the fire compartment, the fire and flame with the last two having their different behaviour due to the presence of no forced draught or forced draught in the compartment. Also included are the heat transfer mechanisms involved in the process and the method of determining the configuration factor for the steel elements. Also developed was a methodology, with its respective fluxogram to determine the increased temperature of the external steel element. Finally some examples are presented, which were elaborated aiming to illustrate the methodology presented.